Documentation as a Methodical Tools in Accounting: Prospects for Electronic Documentary Cooperation Implementation (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article focuses on the information provision of the accounting system at the stage of documenting and subsequent basic data processing. Primary accounting as the initial stage of the accounting process forms operational information for the management system of the entity. Effective organization of primary accounting is primarily due to the efficient organization of document circulation. Thanks to its importance, document circulation is distinguished by a separate sphere of the enterprise activity, the subject area of which is the speed of documents circulation. The documents flow optimizing significantly increases the efficiency of business processes, since there is a direct relationship between the effectiveness of storing information, the possibility and speed of search in the database of the necessary data, modern security of users of the operational data system.It radically changes the very procedure of document flow, including the organization of primary accounting, the application of new information technologies.The advantage of electronic document flow is that offices are getting rid of a large volume of paper documents, and hence problems associated with their use (loss of documents, complexity of changes, distributed access).An electronic document that has been drawn up in accordance with the requirements of the current legislation and contains all the necessary details has the same legal validity as a document drawn up in paper form.Electronic document flow is the only mechanism for processing documents submitted electronically, implementing the concept of «paperless office work».Since each performer involved in the document flow must have an electronic signature, the document management organized according to all rules has all the advantages and excludes all the shortcomings of paper documents.
Keywords: accounting, methodical method, document, electronic document, electronic document flow, electronic digital signature, primary accounting